FTA531 : Music, performance theory and style / Faculty of Film, Theatre and Animation - UiTM, Faculty of Film, Theatre and Animation (Universiti Teknologi MARA (UiTM), 2018)
The course exposes students to the techniques of performance (acting) styles in theoretical manner. The performance styles are divided into classical, modern and postmodern. The course also covers basic area of music appreciation. Students will also be introduced to acting performance methods by Constantin Stanislavski, Bertolt Brecht, Harold Pinter, David Mamet, Meyerhold, Jerzy Grotowski, Antonin Artaud and Charles Marowitz